Analysis of hybrid switches symmetric flying capacitor multilevel inverter based STATCOM. (October 2021) - Humayun, Muhammad; Khan, Muhammad Mansoor; Hassan, Mahmood Ul; Zhang, Weidong
Highlights: A combination of hybrid switches based sfc inverter is introduced. To achieve high power, a cascaded sfc-mli based statcom approach is presented. Feasibility analysis of igct with igbt for proposed topology. Voltage control analysis for dc-link voltage balancing is proposed. Proposed topology is evaluated with simulated and experimental results. Abstract: Static compensator (STATCOM) based on cascaded H-bridge (CHB) multilevel inverter (MLI) uses a lower number of switches compared to the other topologies. Therefore, it is preferred due to lower switch losses. However, it is possible to reduce further the number of switches and its losses in cascaded STATCOM. In this context, a STATCOM based on a cascaded symmetric flying capacitor (SFC) constituted by IGBT and IGCT is presented in this paper. Furthermore, the common issue of imbalance due to asymmetric switch losses has been resolved by proposing and implementing multistage feedback voltage control with a combination of level-shifted and phase-shifted LS-PS PWM switching techniques. Moreover, the switching and conduction power losses calculations and efficiencies of SFC-MLI based on these semiconductors are also presented. Finally, the experimental results show the effectiveness of the proposed topology and the control strategy.